Analisis Reaksi Ruqyah Syar’iyyah Dan Penanganannya Pada Santri Di Lingkungan Pondok Pesantren Riyadhussolihin, Pandeglang, Banten - Oktafia Saputra, Hendra (Rayah Al-Islam, 2025)
This research is motivated by the reaction during Ruqyah Syar'iyyah therapy on a case study of several students who experienced metaphysical disorders in the environment of Riyadhussolihin Pendeglang Islamic boarding school, Banten. The research was conducted to find out the symptoms of mystical disorders and analyze the reactions during Ruqyah Syar'iyyah therapy and find out the techniques in dealing with these problems. This research is a qualitative field research. The data in this study were obtained through interviews and documentation, which were then processed and analyzed using descriptive analysis techniques. The results of this study are that in the process of ruqyah syar'iyyah therapy there are several reactions which are one of the miracles of Alqur'an prayers as an effective spiritual therapy in overcoming metaphysical disorders that often hinder the learning process of students.